2022
DOI: 10.32604/cmc.2022.018564
|View full text |Cite
|
Sign up to set email alerts
|

Adversarial Neural Network Classifiers for COVID-19 Diagnosis in Ultrasound Images

Abstract: The novel Coronavirus disease 2019 (COVID-19) pandemic has begun in China and is still affecting thousands of patient lives worldwide daily. Although Chest X-ray and Computed Tomography are the gold standard medical imaging modalities for diagnosing potentially infected COVID-19 cases, applying Ultrasound (US) imaging technique to accomplish this crucial diagnosing task has attracted many physicians recently. In this article, we propose two modified deep learning classifiers to identify COVID-19 and pneumonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…However, other image dimensions are also found for ultrasound COVID-19 studies. For example, Karar et al (2021b) resized all ultrasound images to 28×28 pixels to avoid a higher computational overhead. Furthermore, Mateu et al ( 2022), Durrani et al (2022), Muhammad and Hossain (2021), and Gare et al ( 2021) resized their ultrasound images to 254×254, 806×550, 512×512, and 624×464 pixels, respectively.…”
Section: Image Resizingmentioning
confidence: 99%
“…However, other image dimensions are also found for ultrasound COVID-19 studies. For example, Karar et al (2021b) resized all ultrasound images to 28×28 pixels to avoid a higher computational overhead. Furthermore, Mateu et al ( 2022), Durrani et al (2022), Muhammad and Hossain (2021), and Gare et al ( 2021) resized their ultrasound images to 254×254, 806×550, 512×512, and 624×464 pixels, respectively.…”
Section: Image Resizingmentioning
confidence: 99%
“…The augmented data were then used to improve the training of different CNNs to diagnose COVID-19. In addition, 3 (5%) studies used GANs for segmentation of the lung region within the chest radiology images [37,51,57], 3 (5%) studies used GANs for superresolution to improve the quality of the images before using them for diagnosis purposes [30,44,68], 5 (9%) studies used GANs for the diagnosis of COVID-19 [20,58,69,70,72], 2 (4%) studies used GANs for feature extraction from images [19,47], and 1 (2%) study used a GAN-based method for prognosis of COVID-19 [22]. The prevalent mode of imaging is the use of 2D imaging data, and 1 (2%) study reported a GAN-based method for synthesizing 3D data [49].…”
Section: Application Of the Studiesmentioning
confidence: 99%
“…The cycleGAN is an image translation GAN that does not require paired data to transform images from one domain to another. Other popular types of GANs were conditional GAN used by 9 (16%) studies [18,22,24,25,33,37,41,57,60], deep convolutional GAN used by 4 (7%) studies [21,38,43,67], and auxiliary classifier GAN used by 4 (7%) studies [32,40,55,69]. The superresolution GAN was used by 2 (4%) studies [44,68], and 1 (2%) study reported the use of multiple GANs, namely Wassertein GAN, auxiliary classifier GAN, and deep convolutional GAN, and compared their performances for improving the quality of images [31].…”
Section: Application Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations